Complete revascularization of non-culprit lesions in stemi is associated with improved myocardial salvage and reduced microvascular obstruction: a cardiac magnetic resonance study. (25th November 2020) - Calvo, M; Guzman, J; Perez, P; Ortega, L.G; Mendieta, G; Lorenzatti, D; Perez, N; Gavara, J; Marcos Garces, V; Brugaletta, S; Sabate, M; Bodi, V; et al.
Abstract: Background: The COMPLETE trial showed that routine and complete Percutaneous Coronary Intervention (PCI) of non-infarct related artery (non-IRA) lesions in STEMI was associated with a significant reduction in the rates of death or new myocardial infarction. However, whether this benefit is related to improved myocardial salvage and left ventricular (LV) function is unknown. Methods: We prospectively included 465 patients with first STEMI reperfused by primary PCI. Late gadolinium-enhanced Cardiac Magnetic Resonance (CMR) was obtained during admission to measure the area at risk (AAR), IRA-infarct size (IS) as % LV mass, and myocardial salvage index (MSI) as % of AAR. The study was repeated in 392 of them at 6 months follow-up to compute LV volumes and ejection fraction (EF). Results: Patients with three-vessel disease had larger IS than those with two or single vessel disease (25.4±14.5% vs 19.0±13.1% vs 19.0±12.8% LV mass respectively, p<0.05), despite no differences in AAR (33±11% LV mass for all). Accordingly, MSI decreased progressively for one, two or three-vessel disease (42.4±31.4 vs 41.5±30.6 vs 25.1±31.3% AAR respectively, p<0.01). The number of myocardial segments with microvascular obstruction (MVO) was also higher for three-vessel disease (1.9±1.9) than for two (1.1±1.7) or single-vessel disease (1.2±1.8), p<0.05. Mean follow-up EF also decreased progressively with the number of vessels involved (50.7±9.4, 49.1±11.4 and, 44.4±11.2% respectively, p<0.01). A total of 183 patients had multivessel disease. Among them, those with complete revascularization (n=51) had larger MSI (46.4±35.2 vs 34.5±29.3% AAR, p<0.04) and were less likely to have MVO phenomenon (28.6 vs 49.2%, p<0.05). However, no significant differences in the change in EF was observed between both groups (ΔEF:+4.4±6.2 vs +4.3±6.2%, p=0.985 for the interaction). Conclusion: The presence and extent of multivessel disease influence myocardial salvage and MVO following primary PCI in STEMI. Improvement in myocardial salvage in the IRA territory and a reduction in microvascular obstruction may mediate the beneficial effects of complete revascularization. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Fundaciό La Marato TV3 2015303132, FIS PI15/00531. Partially funded with FEDER funds.